Effect of Steroids and Black Seed Oil on Hydrogen PeroxideConcentration and pH of Expired Breath Condensate inAsthmatic Patients (Tikrit Journal of Pharmaceutical Sciences, 2023)
Asthma is a chronic inflammatory disease of airway, with increased worldwide prevalence. This study was conducted the for evaluation the effect of different treatment regimens on expired breath condensate hydrogen peroxide concentration and pH. Patients and methods: Thirty two patients ( 17 male, 15 female), with asthma were examined during exacerbation. Asthma was diagnosed according to American Thoracic Society Criteria. The pH level was increased significantly following treatment with prednisolone. In addition, expired breath condensate hydrogen peroxide in patients with acute attack reduced significantly (P